Asuhan Kebidanan Bayi Baru Lahir Fisiologi di Puskesmas Panincong - Musdalifah Musdalifah; Andini Aulia Ramadhani; Andi Nur Hiqmah; Vinny Alvionita; Herawaty Herawaty; Astuti Astuti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Physiological newborns are babies born with a gestational age of more than or equal to 37 weeks with a body weight of 2500 grams to 4000 grams. During the birth period, many physical and psychological changes begin to occur in the baby's body, therefore it requires careful supervision to determine how to adjust to life outside the womb. The purpose of this study was to apply midwifery physiology care to By "Z" at the Panincong Health Center. The care provided uses the Varney 7 Step Midwifery Care Management approach and forms of documentation through SOAP. The case study conducted on By “Z” revealed that there were no obstacles when implementing Varney's 7 Step Midwifery Care Management approach. Thus, it is easy for caregivers to solve problems related to this. The form of midwifery care provided to By "Z" includes taking anamnesis on the baby's parents, carrying out physical examinations, and providing counseling to the parents, in this case to By "Z"'s mother about how to carry out effective care when caring for babies. This case study uses a descriptive observational method with a Continuity of care approach. The subject is By “Z” newborn. How to collect data anamnesis, observation, examination and documentation. Next, compare the data obtained with the existing theory